Andrushchenko M.І., Osіpov M.Y., Kulikovsky R.A., Kapustіan О.YЕ., Magda Е.S., Akrytova T.О. Designing of the technology of restoration and strengthening of the crankshaft knee-lever presses. Part 1. Analysis of the working conditions, the characteristic - Андрущенко, М. І.; Осіпов, М. Ю.; Куликовський, Р. А.; Капустян, О. Є.; Акритова, Т. О. (Problems of Tribology, 2018)
The analysis of the conditions, nature and mechanisms of wear of the working elements of the crankshaft of the knee-lever press used for semi-dry pressing of refractory and building materials is carried out. It is shown that the surface of the crankpin works under conditions of fatigue fatigue wear. Due to the uneven specific pressure on the cervical surface within one pressing cycle (idle and working stroke), the amount of wear along the circumference is not the same and varies within 1.0-5.0 mm (ovality of the neck section appears). As a result of wear, a gap is formed between the working surface of the neck and the inner surface of the sliding bearing, the degree of dynamism of the pressing mechanism increases, vibrations appear, which negatively affects not only the wear resistance of the surfaces of the parts that are in direct contact, but also the reliability and durability of other press components generally. It has been established that the seats under the rolling bearings and the pinion of the pinion gear wear out as a result of fretting corrosion, as indicated by the presence of small wear products (oxides) in the seating positions. When the critical wear value (hundredths of a millimeter) is reached, slippage of the conjugate surfaces of the shaft and bearings may occur, which leads to intensive adhesion wear and scoring. Keyway groove wears out both as a result of fretting corrosion, and even more as a result of plastic deformation (crushing) of its lateral surfaces. It is advisable to use 40Г2Ф steel as a material for restoring the surface of the crankpin by surfacing, and for metal deposition of seats and fusion of keyed grooves, a metal of the 35СГ type.